FULFILLMENT OF THE CONCEPT A LIVABLE CITY IN TERMS OF PHSICAL ASPECTS IN THE CITY OF SOUTH TANGERANG - Febrian Giovani; Anita S. Wartaman; Herika M. Taki (International Journal on Livable Space, 2021)
South Tangerang Cityranked 5th ofthe Most Livable City Index (MLCI) 2017 in Indonesia based on IA Presearch. However, problems were found in terms of equal distribution of urban facilities and infrastructure. The purpose of this study is to examine the physical aspects of  South Tangerang City (the sub-districts of Pamulang, Setu, and Ciputat) to ensure whether or not they evenly meet the requirements of a livable city. This is a comparative analysis study by contrasting the facts of the availability of infrastructure with those of required in the Minimum Service Standards. Availability indicators comprise the provision of livable houses, provision of educational facilities (elementary, junior high, and senior high schools), provision of health facilities (public health and hospitals), provision of green openspace (public and private), road conditions, drainage network, waste management(drinking waterand waste water). The findings show that the priority programs need to be developed to accomplish South Tangerang City as a livable city on anequal basis.The programs among thers are; the provision ofl ivable houses, the provision of public and green open spaces,as well as waste, drinking water, and waste water management